Estimation of platinum gauzes catalyst for ammonia oxidation in nitric acid production - A. W., NurSulihatimarsyila; T. G., Chuah Abdullah, Dr.; Choong, Thomas Shean Yaw, Assoc. Prof. Dr. Ir.; B., Thayananthan (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/